2013
DOI: 10.1161/hypertensionaha.111.00202
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-Converting Enzyme 2 Priming Enhances the Function of Endothelial Progenitor Cells and Their Therapeutic Efficacy

Abstract: Angiotensin converting enzyme 2 (ACE2) is a lately discovered enzyme catalyzing Angiotensin II into Angiotensin (1-7). Angiotensin II has been reported to impair endothelial progenitor cell (EPC) function and is detrimental to stroke. Here, we studied the role of ACE2 in regulating EPC function in vitro and in vivo. EPCs were cultured from human renin and angiotensinogen transgenic (R+A+) mice and their controls (R-A-). In in vitro experiments, EPCs were transduced with lentivirus-ACE2 (Lenti-ACE2) or Lenti-GF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
111
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(119 citation statements)
references
References 42 publications
7
111
0
1
Order By: Relevance
“…The present study shows that ACE2 overexpression both in vivo and ex vivo by ACE2 adenovirus transduction rescued the impaired EDRs in aortas and FMD in resistance mesenteric arteries from diabetic mice, which was consistent with earlier studies on ApoE -/ -mice and spontaneously hypertensive stroke-prone rats (29,43). Recently, ACE2 priming by the pharmacological activator, xanthenone (XNT), has been shown to protect the function of endothelial progenitor cells in hypertension and diabetes (5,11,18,23). In the present study, we have used a newly discovered ACE2 activator, DIZE (20,40,46), and shown that it enhances ACE2 activity in vitro.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study shows that ACE2 overexpression both in vivo and ex vivo by ACE2 adenovirus transduction rescued the impaired EDRs in aortas and FMD in resistance mesenteric arteries from diabetic mice, which was consistent with earlier studies on ApoE -/ -mice and spontaneously hypertensive stroke-prone rats (29,43). Recently, ACE2 priming by the pharmacological activator, xanthenone (XNT), has been shown to protect the function of endothelial progenitor cells in hypertension and diabetes (5,11,18,23). In the present study, we have used a newly discovered ACE2 activator, DIZE (20,40,46), and shown that it enhances ACE2 activity in vitro.…”
Section: Discussionsupporting
confidence: 92%
“…The present results also indicate that ACE2 upregulation and activation may target NADPH oxidases to lower the vascular ROS level in diabetic mice. In fact, the in vitro results show that activation of the ACE2-Ang (1-7) axis suppressed NOX2 expression and attenuated MAPK activation under hyperglycemic conditions, which agrees with a previous report about its beneficial effects on renal proximal tubular cells (12,52), endothelial progenitor cells (5), and endothelial function (11), Moreover, the downstream antioxidant molecular mechanism initiated by ACE2-Ang (1-7) was investigated. UCP2, which preserves endothelial function in diet-induced obese mice and hypertensive rats (27,57), can be upregulated by ACE2 overexpression in HAECs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Studies involving the activation of ACE2 further confirm the role of ANG-(1-7) axis cardiovascular dysfunction. Either pharmacological or genetic activation of ACE2 improved endothelial migration, and impaired tube formation in renin transgenic mice and endothelial dysfunction in SHR rats (57,58). ACE2 activation has been reported to enhance the reparative function of endothelial progenitor cells in the diabetic condition (59).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we proposed to explore whether overexpressing miR-210 in EPC-EXs would enhance the protective of EPC-EXs. The rationale is based on followings: a) EPC transfusion has therapeutic effects on ischemic stroke [39]; b) The potential mechanisms of stem cell therapy for ischemic stroke have been partially attributed to their released microvesicels or EXs [10,11]; c) EPC-released microvesicels have shown angiogenic function in ECs/EPCs by delivering their carried miR-126 [30]; d) miR-210 has shown therapeutic potential for ischemic disease [18]. To determine the role of miR-210 in EPC-EXs, we successfully produced miR-210 enriched EPC-EXs by transfecting EPCs with miR-210 mimics.…”
Section: Discussionmentioning
confidence: 99%